2020
DOI: 10.1002/gj.3975
|View full text |Cite
|
Sign up to set email alerts
|

The Late Cenozoic crustal shortening in the north‐east margin of the Qilian Shan: Evidence from the Fengle Basin, Gansu Province

Abstract: The northeast margin of the Qilian Shan forms the front of the northeastward expansion of the Tibetan Plateau. Its Cenozoic crustal shortening is significant for understanding the uplift and growth of the Tibetan Plateau. The Fengle Basin, in the northeast margin of the Qilian Shan, is characteristic of the typical regional superimposed deformation in Cenozoic strata, documenting the Cenozoic tectonic evolution process in the northeast margin of the Tibetan Plateau. In this study, we conducted large-scale geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Regional stratigraphic correlation reveals that the Youshashan Formation in the northeast margin of the Qaidam Basin corresponds with the Fengle Formation in Wuwei Basin on the northeast margin of Qilian Mountains (Zhao et al, 2021), as well as with the Zhangenbu Formation in the eastern part of Tibet Plateau's northeast margin (Liu, Hu, et al, 2019). Previous research has indicated that during its deposition, even the Fengle Formation in Wuwei Basin experienced NW–SE tectonic extension (Zhao et al, 2020). Similarly, when deposited, the Zhangenbu Formation was also influenced by NW–SE tectonic extension (Huang et al, 2013; Liu, 2013; Liu et al, 2020; Shi, Dong, Liu, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regional stratigraphic correlation reveals that the Youshashan Formation in the northeast margin of the Qaidam Basin corresponds with the Fengle Formation in Wuwei Basin on the northeast margin of Qilian Mountains (Zhao et al, 2021), as well as with the Zhangenbu Formation in the eastern part of Tibet Plateau's northeast margin (Liu, Hu, et al, 2019). Previous research has indicated that during its deposition, even the Fengle Formation in Wuwei Basin experienced NW–SE tectonic extension (Zhao et al, 2020). Similarly, when deposited, the Zhangenbu Formation was also influenced by NW–SE tectonic extension (Huang et al, 2013; Liu, 2013; Liu et al, 2020; Shi, Dong, Liu, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2020) conducted 1:50,000 geological mapping in the Fengle Basin, Gansu Province, and proposed Late Cenozoic crustal shortening in the northeast margin of the Qilianshan Mountain, where is located the front of the northeastward propagation of the Tibetan Plateau. Their large‐scale geological mapping in the Fengle Basin suggests a two‐phase crustal shortening in the Late Cenozoic.…”
Section: Late Cenozoic Intracontinental Deformationmentioning
confidence: 99%